2006
DOI: 10.1074/jbc.m512657200
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of Transcellular Activities of Secretory Phospholipases A2

Abstract: The mechanisms by which secretory phospholipase A 2 (PLA 2 ) exerts cellular effects are not fully understood. To elucidate these mechanisms, we systematically and quantitatively assessed the activities of human group IIA, V, and X PLA 2 s on originating and neighboring cells using orthogonal fluorogenic substrates in various mixed cell systems. When HEK293 cells stably expressing each of these PLA 2 s were mixed with non-transfected HEK293 cells, group V and X PLA 2 s showed strong transcellular lipolytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The amino acid sequence of the proteolytic cleavage site in sPLA 2 -X is similar to that cleaved by subtilisin-like intracellular processing proteases (76), and in fact, intracellularly activated sPLA 2 -X promotes AA release prior to secretion in HEK293 transfectants (90,92). However, subsequent studies have shown that the active form of sPLA 2 -X is predominantly present in the culture supernatants of sPLA 2 -X-transfected bronchial epithelial cells, fibroblasts, and neuronal cells, leading to the suggestion that certain protease(s) present in serum, secreted from cells, or on cell surfaces may play a major role in the activation of sPLA 2 -X (61).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The amino acid sequence of the proteolytic cleavage site in sPLA 2 -X is similar to that cleaved by subtilisin-like intracellular processing proteases (76), and in fact, intracellularly activated sPLA 2 -X promotes AA release prior to secretion in HEK293 transfectants (90,92). However, subsequent studies have shown that the active form of sPLA 2 -X is predominantly present in the culture supernatants of sPLA 2 -X-transfected bronchial epithelial cells, fibroblasts, and neuronal cells, leading to the suggestion that certain protease(s) present in serum, secreted from cells, or on cell surfaces may play a major role in the activation of sPLA 2 -X (61).…”
Section: Discussionmentioning
confidence: 95%
“…Alternatively, sPLA 2 -V might increase AA release from airway cells in concert with cPLA 2 ␣, an event that has been observed in several cell culture studies (87-89). We do not rule out the possibility that sPLA 2 -V-derived eicosanoids do participate in the process of some pulmonary diseases such as those involving eosinophil infiltration, because sPLA 2 -V released from bronchial epithelial cells facilitates membrane hydrolysis of adjacent eosinophils in co-culture through the transcellular route (90).…”
Section: Discussionmentioning
confidence: 99%
“…7A). Although mast cells express group V sPLA 2 , which reportedly has the potential to act on neighboring cells through the transcellular route after secretion (38,70,71), our study using Pla2g5 Ϫ/Ϫ BMMCs argues against the contribution of this sPLA 2 isoform to coculture augmented fibroblastic PGE 2 production. These observations suggest that AA is released mainly by cPLA 2 ␣ from phospholipids in mast cells, transferred to proximal fibroblasts through the juxtacrine route, and then sequentially metabolized to PGE 2 by fibroblastic mPGES-1.…”
Section: Discussionmentioning
confidence: 49%
“…We also used BMMCs obtained from group V sPLA 2 -null (Pla2g5 Ϫ/Ϫ ) mice, because it has been reported that group V sPLA 2 , which is expressed in BMMCs, is able to promote transcellular eicosanoid synthesis by adjacent cells (38,70,71). As shown in Fig.…”
Section: Mast Cell Cpla 2 ␣ Is Coupled With Fibroblastic Mpges-1-depementioning
confidence: 99%
“…It has been reported that sPLA 2 s can exert cellular effects through different mechanisms (12). Based on the earlier finding that the level of sPLA 2 was elevated in inflammatory exudates (13,14), it was generally thought that sPLA 2 s are released to the extracellular medium in response to specific stimuli and act on different target cells by a transcellular or paracrine mechanism.…”
mentioning
confidence: 99%